(untitled) (Medical Forum Monthly, 2024)
Objective: To ascertain the association of smoking with high fibrinogen level and to necessitate the inclusion of fibrinogen level measurement in cardiovascular risk profile. Study Design: cross sectional study. Place and Duration of Study: This study was carried out in Hematology section of Pathology Department of Government Lady Reading Hospital & Hayatabad Medical Complex Peshawar from June 2011 to December 2011. Materials and Methods: Plasma fibrinogen level was measured in 250 healthy male smokers & 250 non smokers as controls by Claus method using Coagulation analyzer Sysmex 530. All subjects were in age group between 25-55 years. Smokers were categorized into light, moderate and heavy smokers on the basis of number of cigarettes smoked per day. Results: Comparison of plasma fibrinogen level of light, moderate & heavy smokers to the plasma fibrinogen level of non-smokers controls showed highly significant results (p-value 0.002, 0.001 & 0.001 respectively) by using t-test. Similarly comparison of plasma fibrinogen level of light to moderate, light to heavy & moderate to heavy also showed highly significant results (p-value 0.001, 0.001 &0.002, respectively) Conclusion: Smoking is the major factor rising plasma fibrinogen level in smokers and predisposes them to cardiovascular diseases. Fibrinogen level rises as the smoking intensity increases Plasma fibrinogen level assessment should be included in cardiovascular risk profile in general & in smokers in particular